The Sovereignty of the Catholic Church and the Sovereign State. A Field of Tension from the Crisis of the Liberal State to the Lateran Pact, with an Epilogue in art. 7 first Paragraph of the Constitution: Peer-reviewed article (Italian Review of Legal History, 2022)
The essay reconstructs the genesis of the ‘Premise’ to the Lateran Treaty of 1929, in which Two High Parties – the Italian government and the Holy See, with the signatures of Mussolini and Cardinal Gasparri – guaranteed the Church «an indisputable sovereignty even in the international field». Hence the «need to establish [...] the Vatican City [...] with sovereign jurisdiction of the Holy See», and art. 2, «Italy recognizes the sovereignty of the Holy See in the international field as an inherent attribute of its nature, in accordance with its tradition and the requirements of its mission». The essay considers that the jurists – Vittorio Emanuele Orlando, who, as Prime Minister in May-June 1919 attempted a negotiation with the Holy See for the solution of the Roman dispute, and Amedeo Giannini, who was among the first to suggest to Mussolini a «new code of ecclesiastical legislation» – linked the Conciliation to the crisis of the liberal State and to the «different regime», which took office in Italy on October 1922. The essay considers that already in 1925 Alfredo Rocco saw a stumbling block in the ‘two sovereignties’ in the construction of the totalitarian state, even if he declared that he had to abandon the «agnostic disinterest of the old liberal doctrinaire». The essay considers that Rocco remained on the sidelines of the negotiations with the Holy See, because he warned against the recognition of the «sovereign Pope, subject of international law» and of «another State within the State», a principle on which jurists such as Ruffini, Scaduto, Schiappoli, Orlando converged. Secret negotiations were entrusted to Domenico Barone – councilor of State, trustee of the Duce – and Francesco Pacelli, consistorial lawyer and trustee of Cardinal Gasparri; the sovereignty of the Church and its ‘State’ appeared to be at stake. The essay considers that the birth of the Vatican City State complicated the ‘image’ of the Kingdom of Italy as a unitary legal entity, ‘built’ by italian jurists, also defended by Giovanni Gentile in the «Corriere della Sera». The essay shows that Fascism intended to recognize Catholicism as the «dominant religion of the State», in order to strengthen the law of May 13, 1871, no. 214, «on papal guarantees and relations between State and Church», which had foreseen a favor religionis for the Catholic Church. The Conciliation stands out as the culmination of a long historical process, which offered legal form to the role that Catholicism had and would have played for the Italian identity; not by chance in March 1929 Agostino Gemelli celebrated a «new Italy reconciled with the Church and with itself, with its own history and its two-thousand-year-old civilization». The essay shows that the sovereignty of the Church and the Vatican City State were much discussed in the parliamentary debate on the ratification of the Pacts signed on February 11, with the harsh tones of Mussolini, who defined the Church as «not sovereign and not even free». Rocco affirmed that the «fascist regime» recognized «de jure» a sovereignty that was «de facto immutable»; he replied to the «improvised and not sincere zealots of the sovereign State, but anticlerical», that «the State is fascist, it does not abandon any part of its sovereignty». Jemolo and Del Giudice – admirers of the «new foundations of ecclesiastical Law» – grasped the meaning of this ‘armed peace’ between Mussolini and the Holy See. The essay examines the wide debate on the «juridical nature» of the sovereignty of the Church and on the «statehood» of the Vatican City State, between public, ecclesiastical, international law, general theory of the state. It captures a junction in the thought of Santi Romano, not by chance indicated by Giuseppe Dossetti to the Constituent Assembly as who theorized the «principle of the plurality of legal systems». The essay then examines the confrontation on the Italian State as a confessional State, supported by Santi Romano, denied by Francesco Scaduto. Some jurists – Calisse, Solmi, Checchini, Schiappoli – looked to the Lateran Pacts as the terrain for strengthening the sovereignty of the State; Meacci wrote of «the super-confessional state, that is, above all confessions»; Piola and Del Giudice thematized a «confessionist State». Jemolo – who in 1927 defined the «sovereignty of the Church as a possibly insoluble question» – affirmed that, after the Agreements, «our State will not be classifiable among separatist countries, but among confessional ones». The essay then examines the debate on the international sovereignty of the Church – discussed, among others, by Anzillotti, Diena, Morelli – regarding the distinction or unity between the Holy See and the Vatican City State, continuation of the papal state or «new state» – and of the ownership of sovereignty. The essay then focuses on Ruffini’s dilemma, «but what exactly is this State», analyzing one of the last writings of the Turin master, the thought of Orlando, Jemolo, Giannini, a monograph by Donato Donati and one by Mario Bracci, two dense Lectures by Mario Falco on the Vatican city, held in Oxford, the legal system of the Vatican City State by Federico Cammeo, in which the «sovereignty exercised by the Pope» was due to the «special importance» in «Relations with Italy». Among the professors of ecclesiastical law the essay examines the perspective developed in the Constituent Assembly, Giuseppe Dossetti on the Church as a primary juridical order, characterized by absolute sovereignty and autonomy not only in spiritualibus; Jannaccone and D’Avack on the «convergence between ecclesiastical potestas and state sovereignty as a necessary coexistence of the Church and the State and of the relative powers»; a ‘pamphlet’ by Jemolo «for religious peace in Italy», which in 1944 he placed freedom as the architrave of new relations between State and Church. The essay concludes the path of the «word sovereignty» – so Aldo Moro to the Constituent Assembly – in the examination of the suffered text of the first paragraph of Article 7 of the Constitution, with the question defined by Orlando as a «flammable zone». Romanian pluralism was imposed on the ‘ancient liberal statualism’ and on ‘legal monism’; Dossetti recalled the «doctrine of the last thirty years against the exclusivist thesis of the statehood of law». He responded to the objections of Cevolotto, Calamandrei, Croce, Orlando, Nenni, Basso in the name of an «historical fact, the Catholic Church […] original order […] without any compression of the sovereignty of the State». As for the discussed communist vote in favor of art. 7 in the name of «religious peace», Togliatti also recalled Ruffini’s Dispense of 1912 – learned during his university years in Turin – on the «formulation The State and the Catholic Church are, each in its own order, independent and sovereign». Between juridical continuities and political discontinuities, the field of tension between ‘the two sovereignties’ has proved to be one of the constitutive elements of Italian identity, in marking the Italian history of relations between State and Church from liberal Italy to the fascist one to the republican one, in a prism of themes-problems, which still questions us today.
Keywords: Constitutional history of relations between Church and State; History of legal thought in the twentieth century abaut Sovereignty of the Holy See and SCV